Evaluation of the Affordable Food Program in Bandung City Using the CIPP Model - Lestari, Septi; Artisa, Rike Anggun; Nurliawati, Nita; Maulana, Riky Rinaldy (Jurnal Studi Ilmu Sosial dan Politik, 2025)
Objectives: This study aims to evaluate the Affordable Food Movement (Gerakan Pangan Murah, GPM) program in Bandung City, which seeks to stabilize food supply and prices by providing food at prices below the market rate, making it affordable for low- and middle-income communities despite their dependence on external food sources. Research Methodology: This research was conducted using a qualitative descriptive approach based on the CIPP (Context, Input, Process, Product) evaluation model developed by Stufflebeam (1985). Data were gathered through document analysis, observations, and interviews with local government officials and community representatives Results: The findings reveal several challenges: uneven implementation across districts, limited execution in areas affected by stunting and low socioeconomic status, protracted coordination processes, inadequate budgeting, ineffective public communication, and flawed operational mechanisms. These constraints hinder the program’s objective of ensuring access to affordable food for vulnerable populations. Conclusion: The evaluation reveals that the Affordable Food Movement (Gerakan Pangan Murah, GPM) program in Bandung faces challenges in consistent implementation, coordination, and outreach, limiting its effectiveness in assisting vulnerable populations. Comprehensive improvements in program design and management are essential to enhance its impact on food supply stability and community welfare. Limitations: The study’s limitations include reliance on qualitative data from a single region, which may affect the generalizability of the findings to other cities. Contributions: This research provides strategic recommendations to enhance food security programs, supporting policymakers and stakeholders in improving urban food systems and poverty reduction. Implementing these can stabilize food prices and expand access for underserved communities in Bandung.